A novel 28-bp indel in IGF1R gene associated with growth traits across four Chinese cattle breeds. (1st November 2021) - Tang, Jia; Ma, Yilei; Yang, Yu; Jiang, Xiaojun; Li, Longping; Lan, Xianyong; Song, Enliang; Lei, Chuzhao; Wang, Xin; Chen, Hong
Abstract: Insulin-like growth factor 1 receptor ( IGF1R ) is a cell surface receptor, belonging to the tyrosine kinase receptor superfamily. IGF1R plays a role not only in normal cell development but also in malignant transformation, which has become a candidate therapeutic target for the treatment of human cancer. This study aimed to explore insertions and deletions (indels) in IGF1R gene and investigate their association with growth traits in four Chinese cattle breeds (Xianan cattle, Jinnan cattle, Qinchuan cattle and Nanyang cattle). The current paper identified a 28-bp indel by polymerase chain reaction within IGF1R gene. The analysis showed that there was a significant correlation between the locus and the hucklebone width of Nanyang cattle in four periods, in which it was highly correlated at 6, 12 and 18 months. At the age of 6 months, it was also significantly correlated with body height, body weight and body length. Association analysis showed that the locus in Jinnan cattle was extremely significantly correlated with body slanting length and body weight, and significantly correlated with chest circumference. There was no significant correlation between this locus and growth traits of Xianan cattle and Qinchuan cattle. The detected indel in the IGF1R gene was significantly associated with growth traits in Jinnan and Nanyang cattle, and could be used as a molecular marker for growth trait selection.